Ethnobotanical study of Loloh: Traditional herbal drinks from Bali (Indonesia). (1st July 2015) - Sujarwo, Wawan; Keim, Ary Prihardhyanto; Savo, Valentina; Guarrera, Paolo Maria; Caneva, Giulia
Abstract: Ethnopharmacological relevance: Loloh are herbal drinks produced and consumed exclusively in Bali (Indonesia) to prevent and treat different ailments. This is the first study to document plants species used as Loloh, reporting the phytochemical components and pharmacological properties of the most cited plants. Documenting the plants used in herbal drinks in Bali by local communities to treat various ailments (providing some information on phytochemistry and pharmacology of the most interesting plants). Materials and methods: Ethnobotanical data were obtained through semi-structured interviews (individual and group discussions) and questionnaires. Plant specimens were collected, identified and made into herbarium vouchers. Results: A total of 51 plants species (belonging to 32 families) have been documented for their use in the various preparation of Loloh . Different plants and plant parts are used to prepare Loloh to treat heartburn, fever, diarrhea, hypertension, aphthous stomatitis (canker sores), and other minor health problems. These plants are mainly prepared as decoctions, are juiced or simply added to the preparation. The most cited plants (>30 informants) are Alstonia scholaris (L.) R. Br., Blumea balsamifera (L.) DC., Cinnamomum burmanni Nees ex Bl., and Piper betle L. These plants are well studied with multiple demonstrated pharmacological activities (e.g., antimicrobial, anticancer, antidiabetic). Conclusion: The Balinese communities still preserve a rich ethnobotanical knowledge. Several species are well known for their pharmacological properties, but some [such as Pneumatopteris callosa (Blume) Nakai and Dendrocnide stimulans (L. f.) Chew] are understudied and could be promising candidates for further research. Graphical abstract: